Influence of divergent length on the gas-particle flowin dual hose dry ice blasting nozzle geometry - Hidayat Mat, Mohamad Nur (Elsevier, 2020)
A numerical simulation study was performed to examine the effect of nozzle geometry and divergent length on gas-particle flows in dual hose dry ice blasting. The simultaneous model of mass momentum and energy exchange between two phases was solved iteratively. The phases are solid dry ice particle and compressible air fluid as a working medium. The results were presented in the gas flow field along the nozzle centerline. The results showed that increasing divergent length decreases the gas-particle density along the centerline; and the density development along the nozzle centerline decreased along the length. Eddy viscosity of the nozzle cavity was steady for length of 0.25 m, but increased drastically for higher values. The substantial increase in eddy viscosity after that position is due to the mixing flow between dry ice pellet and compressed gas which is diverging out from the nozzle outlet area. Thus, the mixing flow experienced back pressure from the atmospheric pressure. The particle mass concentration decreased by increasing nozzle centerline coordinates. The pressure increased along the length; however, it dropped at the end due to the reverse pressure. The temperature increased steadily because of conversion of turbulence to internal thermal energy. The characteristics of gas-particle flow in the nozzle cavity provide better understanding of multiphase flow in turbine and jet engine flow analysis.